Faktor Risiko Krisis Identitas pada Remaja - Firda Raihani; Ulfa Azizah (Faletehan Health Journal, 2025)
Adolescents are particularly vulnerable to experiencing identity crisis due to their inability to resolve internal conflicts effectively. The emergence of an identity crisis can be influenced by several factors, including the roles of parents, teachers, classmates, close friends, and other individuals within the school environment. This research aimed to identify the risk factors associated with identity crisis among adolescents. It used a quantitative research method with a cross-sectional design and chi-square statistical analysis. The sample consisted of 175 students of a junior high school from grades 8 and 9, selected through cluster random sampling technique. Data were collected using Child and Adolescent Social Support Scale (CASSS) and an identity crisis questionnaire. The findings indicated that 79% of respondents experienced a moderate level of identity crisis. There was a significant correlation between identity crisis and the roles of parents (p=0.001), teachers (p=0.001), classmates (p=0.001), close friends (p=0.001), and other individuals in the school environment (p=0.001). To conclude, most adolescents experience a moderate-level identity crisis. Low levels of support from parents, teachers, peers, and the school environment were correlated with the increased risk of identity crisis in adolescents.